Jan Kořenský - Scientist and Man - Uličný, Oldřich (Bohemica Olomucensia, 2024)
This article discusses the scientific and human profile of Professor Jan Kořenský. He was a leading Czechoslovak and Czech linguist and created a new concept of describing the Czech language. It is based on a synthesis of older structuralist and more recent pragmatic and philosophical approach to Czech and language in general. Key words: Jan Kořenský; philosophy of language; pragmatic; cognitive and semiotic approach to Czech and language in general